2017
DOI: 10.1038/s41598-017-10335-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of toxic Microcystis aeruginosa on the silver carp Hypophthalmichtys molitrix revealed by hepatic RNA-seq and miRNA-seq

Abstract: High-throughput sequencing was applied to analyze the effects of toxic Microcystis aeruginosa on the silver carp Hypophthalmichthys molitrix. Silver carps were exposed to two cyanobacteria species (toxic and non-toxic) for RNA-seq and miRNA-seq analysis. RNA-seq revealed that the liver tissue contained 105,379 unigenes. Of these genes, 143 were significantly differentiated, 82 were markedly up-regulated, and 61 were remarkably down-regulated. GO term enrichment analysis indicated that 35 of the 154 enriched GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…PPP1R3G deletion accelerates the metabolic rate and reduces the glycogen level in adipose tissue in mice, indicating that PPP1R3G links glycogen and lipid metabolisms in vivo ( 29 ). In fish (silver carp Hypophthalmichthys molitrix ), a study found that after a treatment with toxic Microcystis aeruginosa , PPP1R3G was down-regulated, indicating that it might play a major role in the detoxifying and antitoxic mechanisms of microcystin in fish ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…PPP1R3G deletion accelerates the metabolic rate and reduces the glycogen level in adipose tissue in mice, indicating that PPP1R3G links glycogen and lipid metabolisms in vivo ( 29 ). In fish (silver carp Hypophthalmichthys molitrix ), a study found that after a treatment with toxic Microcystis aeruginosa , PPP1R3G was down-regulated, indicating that it might play a major role in the detoxifying and antitoxic mechanisms of microcystin in fish ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that oral administration of MCs to fish led to hepatic necrosis and death (Tencalla et al, 1994). Hu et al (2017) evaluated the effects of M. aeruginosa toxicity on Hypophthalmichtys molitrix (silver carp) by using hepatic RNAseq and miRNA-seq. Furthermore, it has been reported that M. aeruginosa alters some biochemical markers of Oreochromis niloticus (Marzouk et al, 2013).…”
Section: Impacts Of M Aeruginosa On Other Living Organismsmentioning
confidence: 99%
“…In addition, another study reported that the biological relationship between PPP1R3G and Sorcin could be related to the calcium, glucose, and lipid homeostasis [ 10 ]. A study also found that the PPP1R3G was downregulated after treatment with toxic Microcystis aeruginosa, suggesting that it plays a critical role in detoxification, along with the antitoxic mechanisms of microcystin in fish [ 11 ]. Researchers found that PPP1R3G was upregulated in transcripts after GCRV infection in grass carp, which indicated that PPP1R3G plays a negative role in anti-GCRV immune responses [ 12 ].…”
Section: Introductionmentioning
confidence: 99%